Analisis Kausalitas Indeks Pembangunan Manusia, Pertumbuhan Ekonomi dan Pariwisata di Indonesia - Martius Martius; Zul Azhar; Ariusni Ariusni (Ecosains: Jurnal Ilmiah Ekonomi dan Pembangunan, 2019)
This research to analyze the causality relationship between Human Development Index, Economic Growth, dan Tourism in Indonesia. The data use are panel from 33 provinces in Indonesia during the period 2011-2016. Data analysis tools use are Panel Vector Autoregression (PVAR) and Granger Causality Panel. The result of this study show that (1) There is a direct causal relationship where Economic Growth effects the Human Development Index, (2) There is a direct causal relationship where Human Development Index influences Tourism, (3) There is no causality between Economic Growth affecting Tourism. Suggested to the giverment should pay more attention to Human Captial in Indonesia, because with better human capital can inrease human development, per capita income can even manage Tourim Indonesia better.